Does cash for school influence young women's behavior in the longer term? Evidence from Pakistan - Andaleeb Alam; Javier E. Baez; Ximena Del Carpio (Institute for the Study of Labor (IZA), 2011)
The Punjab Female School Stipend Program, a female-targeted conditional cash transfer program in Pakistan, was implemented in response to gender gaps in education. An early evaluation of the program shows that the enrollment of eligible girls in middle-school increased in the short term by nearly 9 percentage points. This paper uses regression discontinuity and difference-in-difference analyses to show that five years into the program implementation positive impacts do persist. Beneficiary adolescent girls are more likely to progress through and complete middle school and work less. There is suggestive evidence that participating girls delay their marriage and have fewer births by the time they are 19 years old. Also, girls who are exposed to the program later-on, and eligible for the benefits given in high school, increase their rates of matriculating into and completing high school. The persistence of impacts can potentially translate into gains in future productivity, consumption, inter-generational human capital accumulation and desired fertility. Lastly, there is no evidence that the program has negative spillover effects on educational outcomes of male siblings.
urn:nbn:de:101:1-201105306267
Keywords: I25; J13; J21; O15; 330; conditional cash transfers; female education; female labor participation; fertility; Pakistan